The Implementation of the Child-Friendly Integrated Public Space Program (RPTRA) in Taman Jokowi, West Manokwari District - Marshush, Ummi Hanifah; Hilmi Hilmansyah; Raful Ahmad Madaul (Jurnal Dialektika: Jurnal Ilmu Sosial, 2024)
Urban areas as centers of development and civilization will not be separated from the pressure of increasing built-up land. This condition makes it increasingly urgent for open spaces to be transformed into built-up land. As a result, there is a reduction in green open space, especially as a children's play area. From this condition, the concept of the Child-Friendly Integrated Public Space Program (RPTRA) emerged which has begun to be implemented in several cities or districts, one of which is Jokowi Park in the West Manokwari district. Jokowi Park is quite often visited by the public but is not yet equipped with sports facilities, play facilities and others. So it is not easily accessible to the public, especially children. Based on this, it is important to conduct research related to the implementation of the RPTRA program in Jokowi Park, West Manokwari district. This research was conducted using qualitative methods by collecting opinions from managers, visitors and local residents regarding the components of safety, health, comfort, ease of accessibility, security and beauty. Based on the results of the analysis, there are five components that indicate that Jokowi Park is not good at implementing the Child-Friendly Integrated Public Space Program (RPTRA) concept.